Analysis of Field Inspection Issues and Some Suggestions for Software as Medical Device - Yiqiang YANG; Zhijin FAN; Shuting GUO (Zhongguo yiliao qixie zazhi)
With the encouragement of policies and the rapid development of the biopharmaceutical industry, the number of software as medical device (SaMD) registration applications in Shanghai has continued to increase in recent years, and this paper summarizes the GMP nonconformities found in the field inspection of SaMD in Shanghai from 2020 to 2023, and the results show that nearly 70% of the problems were found in the software development process. Through in-depth analysis, this paper proposes the corresponding countermeasures for the problems found in the five most common stages such as software requirements, software design, software testing, software defect management and software configuration management, combined with the characteristics of software development. These suggested measures have certain reference significance for medical device software development and quality control personnel, and technical reviewer and inspectors.